Implementasi Human-Centered Design dalam Perancangan Front-End Website Fundraising e-YM - Pangestu, Yoga; Yusuf, Dianni; Wibowo, Galih Hendra (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
LAZNAS Yatim Mandiri has achieved various successes in managing, distributing, and empowering underprivileged and underprivileged orphans. Despite this, the Banyuwangi branch still faces challenges in archiving programs, which are currently done conventionally. The Banyuwangi branch of the Yatim Mandiri Foundation has not yet adopted an electronic platform for archiving files and documentation of program distribution, making it difficult for donors to monitor and understand the flow of funds they donate. This research proposes the development of a web-based Yatim Mandiri (e-YM) electronic system to increase the effectiveness and efficiency of program archiving. The design process will be created using Figma software, and the design will refer to the Human Centered Design (HCD) method. The design testing method uses a system usability scale (SUS) to measure and evaluate system usability based on user perceptions. Based on the results of testing the e-YM website design using the Human Centered Design Method approach, the results showed that the design answered user needs. This is because the E-YM website has a distribution page to record all distribution of donations, print LPJ, archive, and independently record donations by donors. Apart from that, the usability score on the System Usability Scale test, which was attended by employees of the Banyuwangi branch of the Yatim Mandiri Foundation, students and the wider community produced an average score of 80.2 (excellent) so that the E-YM website can be accepted by users (community and employees).